1990
DOI: 10.1577/1548-8659(1990)119<0894:sflrba>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Summer Food Limitation Reduces Brook and Rainbow Trout Biomass in a Southern Appalachian Stream

Abstract: We assessed salmon id production in summer in a second-and third-order montane stream in eastern Tennessee in 1987. We sampled three stream sections, one containing exclusively brook trout Salvelinusfontinalis. one containing exclusively rainbow trout Oncorhynchus mykiss. and a third with a mixture of both species. Population estimates for July and October 1987 revealed reductions in biomass over the 4-month period that ranged from 31 to 49%, whereas population densities declined by 32-46% during the same peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 15 publications
2
52
1
2
Order By: Relevance
“…It is likely that reduced growth during warm summers occurred because metabolic demands exceeded caloric intake at the higher temperatures. Reduced summer growth rates for trout have been attributed to limited food supplies in several Michigan rivers (Cooper 1953;Ellis and Gowing 1957) as well as in Canadian and Appalachian streams (Cunjak et al 1987;Ensign et al 1990). Cunjak et al (1987) suggested that energy intake during colder winters was reduced by a combination of lower food consumption rates and slower gastric evacuation rates.…”
Section: Regional Influences On Population Dynamicsmentioning
confidence: 99%
“…It is likely that reduced growth during warm summers occurred because metabolic demands exceeded caloric intake at the higher temperatures. Reduced summer growth rates for trout have been attributed to limited food supplies in several Michigan rivers (Cooper 1953;Ellis and Gowing 1957) as well as in Canadian and Appalachian streams (Cunjak et al 1987;Ensign et al 1990). Cunjak et al (1987) suggested that energy intake during colder winters was reduced by a combination of lower food consumption rates and slower gastric evacuation rates.…”
Section: Regional Influences On Population Dynamicsmentioning
confidence: 99%
“…In Appalachia, salmonids must cope with periodically poor feeding conditions (Cada et al 1987;Ensign et al 1990;Sweka 2003;Thome 2004) as well as occasional extreme environmental circumstances, such as drought and flooding (Carline and McCullough 2003;Hakala and Hartman 2004). The low productivity of Appalachian headwater watersheds, coupled with natural environmental variability, may affect the population dynamics and growth patterns of salmonids.…”
mentioning
confidence: 99%
“…La gamétogénèse est très consommatrice en énergie, surtout pour les femelles , et le développement des gonades et l'activité de reproduction perturbent l'activité alimentaire (WOOTTON, 1999). L'effet de la maturation gonadique se retrouve dans notre étude au niveau des coefficients de condition, qui diminuent dès la fin de l'été, phénomène déjà observé (ELLIS et GOWING, 1957 ;ENSIGN et al, 1990). Les coefficients de condition suivent une évolution saisonnière comparable aux résultats obtenus par de nombreux auteurs (NEVEU et THIBAULT, 1977 ;NEOPHITOU, 1986 ;PREALL et RINGLER, 1989 ;ENSIGN et al, 1990).…”
Section: Discussionunclassified